Risperidone in non‐epileptic attack disorder and chromosome 15q deletion syndrome. Issue 4 (8th November 2021) - Javaid, Amir; Kent, David; Bone, Joanne; Michael, Dasari
Abstract : Chromosome 15q11.2 microdeletion is an emerging syndrome identified in individuals with Prader‐Willi syndrome and Angelman syndrome but also found in isolation. Here, the authors present a case of a 19‐year‐old woman with chromosome 15q11.2 microdeletion and her successful treatment with risperidone, a tailored positive behaviour support plan and with staff training around non‐epileptic attack disorder.